Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1590/0004-282x20170027
|View full text |Cite
|
Sign up to set email alerts
|

High expression of anti-apoptotic genes in grade I and II meningiomas

Abstract: One of the different genetic mechanisms involved in the carcinogenesis of meningiomas is influenced by interactions between proteins that induce and inhibit apoptosis. Objective: To evaluate the expression of c-FLIP, XIAP, Bcl-2, caspase 3, 8 and 9, cytochrome c, APAF 1 and Smac/DIABLO genes related to apoptosis pathways. Methods: The gene expression was evaluated in 30 meningiomas (WHO grades I and II) and in 10 normal samples (from arachnoid tissue) through PCR-RT. Results: The results showed higher expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…FLIP has been shown to be overexpressed in a number of cancer types, including non‐small‐cell lung cancer (NSCLC) , colorectal cancer , pancreatic cancer , nasopharyngeal carcinoma , stomach cancer , meningiomas , urothelial cancer , prostate cancer , acute myeloid leukaemia , Burkitt's lymphoma , cervical carcinomas , ovarian carcinoma and breast cancer . It is also well established that the viral FLIP K13 has antiapoptotic activity and plays an important role in the pathogenesis of gamma‐herpesvirus HHV‐8‐associated tumours, including Kaposi's sarcoma, primary effusion lymphoma and multicentric Castleman's disease .…”
Section: Flip Regulationmentioning
confidence: 99%
“…FLIP has been shown to be overexpressed in a number of cancer types, including non‐small‐cell lung cancer (NSCLC) , colorectal cancer , pancreatic cancer , nasopharyngeal carcinoma , stomach cancer , meningiomas , urothelial cancer , prostate cancer , acute myeloid leukaemia , Burkitt's lymphoma , cervical carcinomas , ovarian carcinoma and breast cancer . It is also well established that the viral FLIP K13 has antiapoptotic activity and plays an important role in the pathogenesis of gamma‐herpesvirus HHV‐8‐associated tumours, including Kaposi's sarcoma, primary effusion lymphoma and multicentric Castleman's disease .…”
Section: Flip Regulationmentioning
confidence: 99%
“…Valnet-Rabier et al [77] showed that in 32 Burkitt's lymphoma cases, a mainly cytoplasmic pool of c-FLIP was highly correlated with poor patient outcome [77]. Several studies have identified c-FLIP as an independent adverse indicator in cancer and found both c-FLIP L and c-FLIP S play important roles in cancer patient treatment outcomes and that the expression of particular c-FLIP isoforms has prognostic clinical value [66,[78][79][80][81][82][83][84][85][86]. Ullenhag et al [87] showed in colorectal (CLR) cancer patients that c-FLIP L is an independent marker of poor prognosis.…”
Section: C-flip As a Valuable Prognostic Biomarker In Various Cancersmentioning
confidence: 99%
“…Additionally, another protein and gene expression analysis focused on apoptotic pathways including c-FLIP, XIAP, Bcl-2, caspase 3, 8 and 9, cytochrome c, APAF 1 and Smac/DIABLO molecules reported low protein levels regarding caspases. The study group also identified a potential blocking of these apoptotic inducers mediated by c-FLIP inhibition on them [ 16 ]. Interestingly, specific polymorphisms affecting genes such as caspase 8, NF2, XRCC1, and BRIP1 are related to increased risk for meningioma rise [ 17 ].…”
Section: Discussionmentioning
confidence: 99%